2020
DOI: 10.3389/fneur.2020.582891
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Neurodevelopment in Infants With Tuberous Sclerosis Complex Using Early EEG Characteristics

Abstract: A dysmature EEG background was also associated with lower cognitive (p-value = 0.029), language (p-value = 0.001), and motor (p-value = 0.017) developmental quotients at the age of 24 months. Our findings suggest that early EEG characteristics in newborns and infants with TSC can be used to predict neurodevelopmental comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 47 publications
(72 reference statements)
1
26
0
1
Order By: Relevance
“…Thus, we speculate that the presence of inhibition-dominated networks in TSC may relate to neurodevelopmental delay and cortical dysfunction (e.g., due to cortical tubers and aberrant surrounding tissue). Indeed, signs of cortical dysfunction, dysmaturity, and epilepsy [e.g., as reflected by slowing of activity ( Krsek et al, 2010 ; Terney et al, 2010 ; Tao et al, 2011 ; Stoner et al, 2014 ; Britton et al, 2016 )] have been described in EEG recordings in TSC ( De Ridder et al, 2020 ). Importantly, we have previously associated EEG abnormalities to low f E/I in ASD ( Bruining et al, 2020 ) and in children with STXBP1 syndrome, which is another genetic disorder with a high prevalence of epilepsy ( Houtman et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we speculate that the presence of inhibition-dominated networks in TSC may relate to neurodevelopmental delay and cortical dysfunction (e.g., due to cortical tubers and aberrant surrounding tissue). Indeed, signs of cortical dysfunction, dysmaturity, and epilepsy [e.g., as reflected by slowing of activity ( Krsek et al, 2010 ; Terney et al, 2010 ; Tao et al, 2011 ; Stoner et al, 2014 ; Britton et al, 2016 )] have been described in EEG recordings in TSC ( De Ridder et al, 2020 ). Importantly, we have previously associated EEG abnormalities to low f E/I in ASD ( Bruining et al, 2020 ) and in children with STXBP1 syndrome, which is another genetic disorder with a high prevalence of epilepsy ( Houtman et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…in the latent period), has been determined to be a reliable prognostic biomarker for later epilepsy and indeed neurodevelopmental comorbidities ( Figure 1 ). 37 39 Crucially, this discovery has been instrumental in the design of clinical trials focussed on epilepsy prevention, including the EPISTOP and PREVeNT trials that are described below. In addition, in line with current European guidelines for infants and children to receive regular EEG monitoring, 17 a recent study showed that conducting at least one EEG study in TSC patients before epilepsy onset and continuing with regular EEG monitoring is now the standard of care in many centres, while it is becoming more common for clinicians to prescribe ASDs prophylactically when epileptiform discharges occur on EEG before the emergence of clinical seizures.…”
Section: Tsc-associated Epilepsy and Neuropsychiatric Disordersmentioning
confidence: 99%
“…Five studies did not report significant findings after covariate adjustment. [19][20][21][22][23] Significant results are summarized in Figure S2a (online supporting information).…”
Section: Cognitive Outcomementioning
confidence: 99%